Perancangan Website Company Profile pada UMKM Orazio Multiusaha Indonesia - Suci, Suci (Applied Business and Administration Journal, 2022)
Orazio Multiusaha Indonesia is an MSME engaged in fashion and located in Bandung. It has been running since 2015 until now, but the lack of company information that is spread to the public, especially for prospective customers, partners and resellers is an obstacle for MSMEs to move to reach more target markets. From the perceived constraints, a company profile website was created using the WordPress CMS. The purpose of making this company profile website project is as a medium of information for prospective customers, partners and resellers, besides that this company profile website is also used as a medium of communication between the company and its target market. The design stage begins with observation and then interviews with MSME owners. The results of trials and interviews with MSME owners regarding the design of the company profile website have been assessed according to the company's needs. This is indicated by the results of interviews using the end-user computing method which shows that the website design has met the needs. The information listed on the website can help the company as a medium for disseminating information, and as a medium for communicating with customers. However, there are some suggestions that must be made when creating a company profile website. MSME owners Orazio Multiusaha Indonesia also need to carry out optimal management so that the function of the website as a medium of information and communication continues.